Cardiac response to enzyme replacement therapy in infantile Pompe disease with severe hypertrophic cardiomyopathy. Issue 4 (7th March 2017) - Avula, Sravani; Nguyen, Thuylinh M.; Marble, Michael; Lilje, Christian
Abstract : Classic infantile‐onset Pompe disease (IOPD), characterized by predominantly cardiac involvement, used to be considered uniformly lethal within months. The availability of enzyme replacement therapy (ERT) has transformed the course of the disease. Decrease in ventricular hypertrophy and improvement in ventricular function have been suggested as proof for efficacy. We report the cardiac response to ERT of a child with IOPD and severe hypertrophic cardiomyopathy. The myocardial hypertrophy resolved. Change in ejection fraction, however, was slow. We discuss the potential benefit of other parameters beyond ejection to assess cardiac function in IOPD, including speckle tracking‐based strain.